Seasonal Variations and Dietary Protein-Energy Levels: Effects on Laying Quails under Subtropical Conditions - Ashour, EA; Aldhalmi, AK; Youssef, IM; Elsherbeni, AI; Attia, YA; Bovera, F; Addeo, NF; Alhotan, RA; Abd El-Hack, ME (Journal of the Hellenic Veterinary Medical Society, 2025)
Optimizing the diet of laying Japanese quail (Coturnix japonica) is essential to enhance their productivity. The experiment evaluated the efficiency, digestive parameters, and nutrient composition of laying Japanese quail during warm and cold months under subtropical conditions, in relation to the amounts of crude protein (CP) and metabolizable energy (ME). A randomized experimental design was used, involving 360 laying Japanese quail assigned to nine treatment groups, each with five replications of eight hens each across two independent experiments conducted during cold and warm seasons. Variations in protein and energy concentrations significantly impacted multiple production performance metrics, such as egg mass (EM), cost-effectiveness and feed conversion ratio (FCR). Quails showed the highest FCR and EM measurements when fed a diet with 2900 kcal/kg and 22% CP during the cold season, and 3000 kcal/kg with 20% CP during the warm season. Protein and energy levels significantly impacted egg quality and digestion ratios of dry matter (DM) and ether extract (EE). For optimal growth and overall health, Japanese quail should be fed a summer diet containing approximately 20% crude protein and 3000 kcal ME/kg. Adjusting the protein and energy content in the feed can enhance the performance and nutrient efficiency of laying Japanese quail, particularly in seasonal conditions, thereby informing feeding strategies for better production outcomes.